Investigating the Role of Digital Literacy on Language Students' Survival Skills in Distance Learning - Butac, Maylyn; Macapia, Charmaine; Galapon, Mae Angelyn; Bernabe, Claire; Soriano, Rhea; Diamsay, Maridel; Andam, Crizelda; Mendoza, Aidie; Tumamao, Chabelita; Lacaste, Apol Jean; Cariño, Joshua (International Journal of Arts, Sciences and Education, 2022)
Abstract: The rapid advancement of digital technology necessitates the development of digital literacy skills that can assist students in surviving their distance learning experiences. In this context, this mixed-method study aimed to investigate how language students integrate digital literacy into their distance learning classroom and what digital literacy skills they frequently practiced. This research employed descriptive statistics design. The respondents of the study were the language students at the university and were chosen purposively. The research instrument utilized was the web-based survey using Google Form. The quantitative findings revealed that language students frequently integrate digital literacy into their distance learning. Meanwhile, digital literacy skills in terms of understanding digital practices, finding information, using information, and creating information were also frequently practiced by the respondents. The qualitative data suggested that language students have demonstrated positive integration of digital literacy into their distance learning; thus, the researchers concluded that digital literacy skills are needed to survive in distance learning classrooms.